El Excentrico, 1960-12-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
December 5, 1960 [5 de diciembre de 1960] Ano 11, No 4. Cover has photographs of landmarks in Guadalajara, Jalisco. The headline reads, "Historic landmarks in Guadalajara, Jalisco."